Construction and validation of an instrument for nursing consultation for patients from target groups or with chronic kidney disease in primary health care (Research, Society and Development, 2021)
The study aimed to build and validate an instrument for nursing consultation to patients from target groups or with chronic kidney disease in Primary Health Care. This is a methodological research of the development of tools type. The study was carried out in four phases: 1. Construction of the instrument based on an integrative literature review, 2. Conception of the instrument that covered the stages of the nursing process, 3. Recruitment of judges to participate in the study, and 4. Content validation regarding the structure, presentation, clarity and relevance of the material with 18 judges. Data analysis was performed based on the Content Validation Index (CVI) and the binomial test to assess the experts' agreement and consistency in relation to the instrument's items. In the statistical analysis, the instrument's global CVI was 0.90 (95%CI: 0.86 – 0.93). When performing the binomial test to identify agreement between the evaluators, it was observed that when an agreement of 80% was stipulated, it was not possible to obtain differences between the judges. As for the evaluation of the items of the nursing consultation instrument, 94.4% (n=17) of the judges considered that all aspects of the history, nursing diagnoses and interventions and results were clear and relevant. It is concluded that the study achieved its objectives regarding the validation of contents such as structure, presentation, clarity and relevance of the material. It was found that all content contained in the instrument was considered significant for improving the quality of nursing consultations for patients from target groups or patients with CKD.